Excitatory synaptic responses in turtle cerebellar Purkinje cells. - Chan, C Y (1989)
1. Climbing fibre responses (CFRs) and parallel fibre responses (PFRs) in Purkinje cells have been analysed in intracellular recordings obtained at various levels from cell body to terminal dendrites in the turtle cerebellum in vitro. 2. With increasing stimulus intensity, the PFR recorded in distal dendrites displayed an early regenerative component which was graded at rest and at hyperpolarized membrane potentials, but was all-or-none at depolarized membrane potentials. 3. The all-or-none component had the same characteristics as Ca2+ spikes triggered by passing depolarizing current through the recording electrode. 4. The repolarizing phase of the PFR had a fast component enhanced by depolarization and diminished by hyperpolarization. 5. In the mid-molecular layer the PFR also included a plateau component which was increasingly prolonged by depolarization and abolished by hyperpolarization. 6. CFRs recorded in the soma had a plateau component, prolonged by local depolarization and abolished by local hyperpolarization. 7. The CFR in distal dendrites included a regenerative component. In some cells this component appeared in an all-or-none manner with local depolarization. In other cells it was smoothly graded with local polarization. 8. In mid-molecular records the CFR was prolonged by local depolarization and presumably electrotonically affected by the configuration of the response more distally and proximally in the cell. 9. It is concluded that excitatory synaptic responses in Purkinje cells include a regenerative Ca2+-mediated spike component in the spiny dendrites and a plateau component located in the proximal dendrites and/or the cell body. It is shown that both responses are modulated in configuration by the local membrane potential. In the spiny dendrites activation and inactivation of the transient hyperpolarizing potential appear to govern the Ca2+ influx during the CFR.